ANALISIS TERHADAP KOORDINASI OTORITAS JASA KEUANGAN DENGAN LEMBAGA LAINYA DALAM PENGAWASAN PERBANKAN BERDASARKAN UNDANG –UNDANG NOMOR 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN - Kartiko, Galuh (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2017)
The Bank, as an intermediary institution, in managing public funds should be conducted with sufficient expertise, so that public trust is maintained and there is no withdrawal of public funds deposited in banks that may result in economic activities. The presence of an institution that serves to oversee banking institutions is needed to ensure public trust so that banking management can be done in accordance with the rules of banking management is good and true. The existence of an independent authority becomes the determining factor in the smooth operation of the financial services sector. With the formation of the Financial Services Authority, it is expected to solve problems arising from the complexity of the existing financial system in Indonesia and to reorganize the organizational structure of the institutions Which carries out regulatory and supervisory tasks in the financial services sector covering the banking sector, capital markets, insurance, pension funds, financial institutions and other financial services institutions. Structuring is done in order to achieve a more effective coordination mechanism in dealing with problems arising in the financial system, thus ensuring the achievement of financial system stability. The regulation and supervision of the entire financial services activities must be done in an integrated manner.